CRIME IN EKA KURNIAWAN’S NOVEL LELAKI HARIMAU - Nasution, Sahmin; Siwi, Purwnto; Pardi, Pardi (Universitas Islam Sumatera Utara, 2024)
The novel Lelaki Harimau by Eka Kurniawan describes the life of Javanese people during the Japanese colonial period. In the novel, there are various kinds of social problems, one of which is crime. This research aims to describe the forms of crime in the novel. This research uses a qualitative descriptive method with data collection techniques in the form of library research. The theory used is criminal psychology with a literary psychology approach to bridge the study of psychology and literature. The results of the research show that there are three forms of crime in the novel: domestic violence, sexual harassment and rape committed by the major characters. The domestic violence as well as raping is done by a husband towards his wife; something weird but that is the truth. Sexual harassment is experienced by other female characters owing to hegemony of power and money. The research shows that crime is one of the social problems that occurs in society. These crimes can be caused by various factors, such as poverty, social inequality and family conflict.